2021
DOI: 10.1111/bjh.17801
|View full text |Cite
|
Sign up to set email alerts
|

Mimics and artefacts of measurable residual disease in a highly sensitive multicolour flow cytometry assay for B‐lymphoblastic leukaemia/lymphoma: critical consideration for analysis of measurable residual disease

Abstract: High-sensitivity multicolour flow cytometry (MFC)-based B-lymphoblastic leukaemia (B-ALL) measurable residual disease (BMRD) assay is increasingly being used in clinical practice. Herein, we describe six consistently present low-level populations immunophenotypically mimicking abnormal B-ALL blasts in 441 BMRD samples from 301 children. These included CD19 + CD123 + plasmacytoid dendritic cells differentiating from lymphoid precursors, CD10 + transitional B cells with CD10 + / CD38dim-to-negative/CD20bright/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…These cells are described in Figure 1, Figures S1 and S2, and Table 2. Plasmacytoid dendritic cell (pDC) precursors differentiating from B‐lymphoid cells (pDC‐LP): This population showed a distinctly bright expression of CD123, intermediate expression of CD304 and HLA‐DR, and heterogeneous expression of CD34 and B cell markers CD10/CD22/CD24/CD81. We have previously described these cells as plasmacytoid dendritic cell (pDC) precursors differentiating from B‐lymphoid cells (pDC‐LP) 31 . Since CD123 and CD304 are leukemia‐specific aberrant markers in BMRD assay, these cells can be confused with MRD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are described in Figure 1, Figures S1 and S2, and Table 2. Plasmacytoid dendritic cell (pDC) precursors differentiating from B‐lymphoid cells (pDC‐LP): This population showed a distinctly bright expression of CD123, intermediate expression of CD304 and HLA‐DR, and heterogeneous expression of CD34 and B cell markers CD10/CD22/CD24/CD81. We have previously described these cells as plasmacytoid dendritic cell (pDC) precursors differentiating from B‐lymphoid cells (pDC‐LP) 31 . Since CD123 and CD304 are leukemia‐specific aberrant markers in BMRD assay, these cells can be confused with MRD.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach is expected to yield a more prominent cluster of residual leukemic B‐blasts. However, we have previously reported that such acquisition of a higher number of cells may also pose problems in interpretation as consistently occurring low‐level cells in BM may immunophenotypically mimic residual leukemic B‐blasts 31 . CD22 is also weakly expressed in non‐B cells such as basophils, mast cells (MC), and plasmacytoid dendritic cells (pDC) 32–34 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells with overlapping immunophenotype like plasmacytoid dendritic cells, CD10+ transitional B cells, CD19+ natural killer (NK) cells, mesenchymal stromal/stem cells, as well as endothelial cells could well interfere with the rare true residual leukemic cells and should be kept in mind. 32 There is no clear recommendation yet on the number of cells in a cluster required to define residual disease; however, most of the studies in B-ALL indicate a minimum number between 10 and 50 events. 33 Majority of the treatment protocols agree upon 0.01% clinically defined threshold to define MRD positivity.…”
Section: Mrd In B-allmentioning
confidence: 99%
“…An additional by‐product of acquiring a large number of cells is that the normal bone marrow components are also acquired in large numbers. This gives rise to consistent artefacts such as CD19‐positive plasmacytoid dendritic cell precursors, CD10‐positive transitional B cells, CD19‐positive natural killer (NK) cells and others 8 . Therefore, standardization across various centres in processing, acquisition and analysis strategies becomes even more important for the widespread use of MFC‐BMRD with high sensitivity.…”
Section: Figurementioning
confidence: 99%
“…This gives rise to consistent artefacts such as CD19-positive plasmacytoid dendritic cell precursors, CD10positive transitional B cells, CD19-positive natural killer (NK) cells and others. 8 Therefore, standardization across various centres in processing, acquisition and analysis strategies becomes even more important for the widespread use of MFC-BMRD with high sensitivity. The EuroFlow group has published their protocols, panels and analysis strategies for relatively easy implementation in other centres.…”
mentioning
confidence: 99%